Chiral Amino Alcohol Accelerated and Stereocontrolled Allylboration of Iminoisatins: Highly Efficient Construction of Adjacent Quaternary Stereogenic Centers. Issue 17 (24th March 2017) - Tan, Qiuyuan; Wang, Xinqiao; Xiong, Yang; Zhao, Zimeng; Li, Lu; Tang, Pei; Zhang, Min
Abstract: We have developed a highly efficient asymmetric allylboration of ketimines with nonchiral γ, γ‐disubstituted allylboronic acids by using a chiral amino alcohol as the directing group, which is otherwise challenging. The amino alcohol not only serves as a cheap source of nitrogen and chirality, but also dramatically enhances the reactivity. The versatility of this method was demonstrated by its ability to access all four stereoisomers with adjacent quaternary carbon centers. A reaction model was proposed to explain the diastereoselectivity and the rate‐accelerating effect. Abstract : Collect the full set of four ! A chiral amino alcohol was used as the directing group for the asymmetric allylboration of ketimines with nonchiral γ, γ‐disubstituted allylboronic acids (see scheme). The amino alcohol not only serves as a cheap source of nitrogen and chirality, but also dramatically enhances reactivity. This versatile method can be used to access all four stereoisomers of a product with respect to the adjacent quaternary carbon centers.